Radiological dose assessment for the leaking coil replacement on the Necsa radioactive effluent evaporator facility - Kros, Charles (My University, 2014)
In this study a dose assessment is used to demonstrate conformance to national and international dose limits for workers and meets the Necsa ALARA goals for a radiological repair task. The dose assessment methodology is based on international standards, principles and criteria and involves the process of determining radiological dose, through the use of exposure scenarios, bioassay results, monitoring data, source term information, and pathway analysis. The radiological task is the replacement of the leaking steam coil on the radioactive effluent evaporator facility at Necsa. The effluent treatment facility, its operation, the origin of the radioactive effluent and hazards associated with the leaking coil are discussed. The dose assessment is supported by measurement of actual radiological conditions in the area where the task will be performed using suitable and calibrated instrumentation. The assumptions were limited to the physical phenomena associated with the behaviour of materials and available from national and international studies. The importance of proper planning of all the tasks associated with the replacement task as well as sources of inaccuracy and uncertainty associated with the calculated doses are discussed. The results of the assessment are evaluated in terms of ALARA, namely the safety fundamental principles of justification, optimisation and limitation of facilities and activities. Other dose reduction options, such as personal protective clothing and equipment, were considered to show that the doses conform to the ALARA objectives of Necsa and other operation optimisation measures.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 2013.
Keywords: Ionizing radiation.; Radiation - Safety measures.; Ionizing radiation - Measurement.